Behavior of a Sandwich Beam Subjected to Bending in Terms of the Core‘s Shape and Density - Ruzica R. Nikolic; Jelena M. Djokovic; Jan Bujnak (Communications - Scientific letters of the University of Zilina, 2016)
Problem of the multi-layer sandwich beams, subjected to bending, is considered in this paper. The influence of the density and shape of the sandwich beam core on the beam behavior was studied. The two beam configurations were analyzed: the beam whose cross-section is constant along its length and the beam with periodically varying cross-section along the length. Each of the two configurations was considered for the two different core shapes – with the square and the circular holes. The diagrams of the beam deflection in terms of the number of the core unit cells are presented for the two beam configurations and the two core shapes. Based on results presented in this paper, one can conclude that in the given loading conditions, the core density, after reaching certain critical value, ceases to affect the bent sandwich beam behavior. Comparison of the two cores shapes leads to conclusion that, in the same loading conditions, the core with the square holes provides for the better sandwich beam‘s characteristics, i.e. such a beam has smaller deflection with respect to the beam with the core with the circular holes.